Kaplan dan Sadock Sinopsis Psikiatri : ilmu pengetahuan perilaku psikiatri klinis Jilid l - KAPLAN, Harold l (Bina Aksara, 1997)
Kaplan dan Sadock Sinopsis Psikiatri : ilmu pengetahuan perilaku psikiatri klinis Jilid l